A German requiem - Kerr, Philip (Kerr, Philip. Bernie Gunther novel., 2006)
In the wreckage of postwar Berlin, PI Bernie Gunther--in his third appearance--accepts coal for payment and reluctantly takes on a case for Russian Col. Palkovich Poroshin, one of the despised "Ivans." Asked to prove black marketeer Emil Becker innocent of the death of U.S. Counterintelligence Corps Capt. Edward Linden, Gunther leaves Berlin (and his unfaithful wife) for Vienna, where the incarcerated Becker insists he had been set up while delivering SS files to Linden at the behest of a stranger named Konig. Gunther's search for Konig attracts the attention of the CIC's John Belinksky, who also believes Becker was framed. After saving Gunther from some drunken Russians, Belinsky asks Gunther to infiltrate the ranks of a super-secret group of ex-Nazis whose leader may be former Gestapo head Heinrich Muller. Obviously, the Nazi-hunting CIC wants Muller badly, but Belinsky drops a bombshell that brings into question his own role in the investigation. Unleashing a series of stunning revelations, Kerr (The Pale Criminal) discloses the reasons for the Russians' interest in Linden and for the many deaths involved in Gunther's case. Rooted in historical details, driven by a powerful narrative, this atmospheric novel traces a frightening course amid a multiplicity of ironies.